A Radical Culture for Children of the Working Class: The Young Socialists' Magazine, 1908-1920 - Tager, Florence (Radical Teacher, 2023)
The Young Socialists' Magazine, published from 1908-1920, was the first radical working-class children's magazine in the United States. In its pages appeared the writings of prominent political figures such as Rosa Luxemburg and Eugene Debs and those of such noted authors as Leo Tolstoy and Maxim Gorky. The lively content of the magazine also included poetry, songs, folktales, essays, and cartoons as well as a revisionist history of the United States from the Revolutionary War through Reconstruction. These features of the 15–18-page newspaper-size magazine were used to construct a working-class cultural identification in children that was tied to radical socialist activity. The cultural articles created role models and an alternative value structure while the political articles forged an allegiance to socialist politics. The unique feature of using sophisticated reading materials for children to develop a cultural identification tied to radical politics provides one model for developing oppositional cultural forms. This model may prove useful to educators today who are redesigning curricular materials to include race, ethnicity, gender, and class perspectives that have been marginalized from mainstream texts.